1998
DOI: 10.1159/000040839
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Effects of Oral Cobalamin Preparations on Patients with Megaloblastic Anaemia

Abstract: We investigated the haematological effects of a massive dose of oral cobalamin (vitamin B12) on patients with cobalamin deficiency anaemia who had severe anaemia with a few neurological impairments and found that oral treatment was almost as effective as conventional injection therapy. The recovery of haematological indices with oral cobalamin preparations was slightly slower than with parenteral preparations, although the subjective symptoms disappeared soon after the start of therapy. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 2 publications
3
8
0
1
Order By: Relevance
“…The response to oral therapy is described among adults as reticulocytosis peaking at 1 week, with correction of WBC, platelets, and MCV after an average of 9.5, 9.7, and 22.4 days, respectively. Hb is usually the last to improve, with values exceeding 10 g/dl within an average of 34.3 days . Our children showed a similar response in all parameters.…”
Section: Discussionsupporting
confidence: 72%
“…The response to oral therapy is described among adults as reticulocytosis peaking at 1 week, with correction of WBC, platelets, and MCV after an average of 9.5, 9.7, and 22.4 days, respectively. Hb is usually the last to improve, with values exceeding 10 g/dl within an average of 34.3 days . Our children showed a similar response in all parameters.…”
Section: Discussionsupporting
confidence: 72%
“…While the current results suggest that oral crystalline cyanocobalamin may be effective for the treatment of cobalamin deficiency related to food cobalamin malabsorption, the treatment duration and the optimal dose of oral cyanocobalamin remain to be determined (Carmel, 1995; Kondo, 1998). In the present study, all patients showed significant responses during the first month of oral cobalamin therapy.…”
Section: Discussionmentioning
confidence: 92%
“…However, clinical response has not been consistently optimal [45]: relapse occurs more when oral cobalamin is discontinued and there is lack of evidence of equivalent neurologic improvement after oral vitamin B12 [46]. In elderly persons with MMA abnormalities, high levels of MMA persist after daily oral intake of vitamin B12 [43,47].…”
Section: Discussionmentioning
confidence: 99%